The Diarylheptanoid Curcumin Induces MYC Inhibition and Cross-Links This Oncoprotein to the Coactivator TRRAP - Mödlhammer, Alexander; Pfurtscheller, Sandra; Feichtner, Andreas; Hartl, Markus; Schneider, Rainer (Frontiers in Oncology, 2021)
The c-Myc protein (MYC) is a transcription factor with strong oncogenic potential controlling fundamental cellular processes. In most human tumors, MYC is overexpressed by enhanced transcriptional activation, gene amplification, chromosomal rearrangements, or increased protein stabilization. To pharmacologically suppress oncogenic MYC functions, multiple approaches have been applied either to inhibit transcriptional activation of the endogenous MYC gene, or to interfere with biochemical functions of aberrantly activated MYC. Other critical points of attack are targeted protein modification, or destabilization leading to a non-functional MYC oncoprotein. It has been claimed that the natural compound curcumin representing the principal curcumoid of turmeric (curcuma longa) has anticancer properties although its specificity, efficacy, and the underlying molecular mechanisms have been controversially discussed. Here, we have tested curcumin’s effect on MYC-dependent cell transformation and transcriptional activation, and found that this natural compound interferes with both of these MYC activities. Furthermore, in curcumin-treated cells, the endogenous 60-kDa MYC protein is covalently cross-linked to one of its transcriptional interaction partners, namely the 434-kDa transformation/transcription domain associated protein (TRRAP). Thereby, endogenous MYC levels are strongly reduced and cells stop to proliferate. TRRAP is a multidomain adaptor protein of the phosphoinositide 3-kinase-related kinases (PIKK) family and represents an important component of many histone acetyltransferase (HAT) complexes. TRRAP is important to mediate transcriptional activation executed by the MYC oncoprotein, but on the other hand TRRAP also negatively regulates protein stability of the tumor suppressor p53 (TP53). Curcumin-mediated covalent binding of MYC to TRRAP reduces the protein amounts of both interaction partners but does not downregulate TP53, so that the growth-arresting effect of wild type TP53 could prevail. Our results elucidate a molecular mechanism of curcumin action that specifically and irreversibly targets two crucial multifunctional cellular players. With regard to their broad impact in cancer, our findings contribute to explain the pleiotropic functions of curcumin, and suggest that this natural spice, or more bioavailable derivatives thereof, may constitute useful adjuvants in the therapy of MYC-dependent and TRRAP-associated human tumors.